A review of glass-ionomers: From conventional glass-ionomer to bioactive glass-ionomer - Maryam Khoroushi; Fateme Keshani (Wolters Kluwer Medknow Publications, 2013)
Materials used in the body, especially the materials used in various oral cavity regions should be stable and passive without any interactions with the body tissues or fluids. Dental amalgam, composite resins and dental cements are the materials of choice with such properties. The first attempts to produce active materials, which could interact with the human body tissues and fluids were prompted by the concept that fluoride-releasing materials exert useful effects in the body. The concept of using the "smart" materials in dentistry has attracted a lot of attention in recent years. Conventional glass-ionomer (GI) cements have a large number of applications in dentistry. They are biocompatible with the dental pulp to some extent. GI is predominantly used as cements in dentistry; however, they have some disadvantages, the most important of which is lack of adequate strength and toughness. In an attempt to improve the mechanical properties of the conventional GI, resin-modified glass-ionomers have been marketed, with hydrophilic monomers, such as hydroxyethyl methacrylated (HEMA). Some recent studies have evaluated GI with bioactive glass in its structure to validate the claims that such a combination will improve tooth bioactivity, regeneration capacity and restoration. There is ever-increasing interest in the application of bioactive materials in the dental field in an attempt to remineralize affected dentin. The aim of this review article is to evaluate these materials and their characteristics and applications.